1975
DOI: 10.1149/1.2134193
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State Anodic Leakage Current in Barrier‐Type Aluminum Oxide Films

Abstract: When aluminum is polarized potentiostatically in a barrier-forming electrolyte, such as aqueous ,ammonium tartrate, the current passed diminishes steadily to a low value commonly termed the leakage current. This value is not stable, but increases gradually, attaining a constant value after many hours. The dependence of this steady-state current on potential has been studied for aluminum electrodes in 1M aqueous ammonium tartrate at pH 7 and test temperatures of 30 ~ 50 ~ and 70~ In the overpotential range of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…1. A series of calibration measurements on small samples of known area showed that -c --KSA [1] where 8A is the area of metal being anodized, and K, for our experimental arrangement, had a value of 300 mse c/cm 2.…”
Section: Reanodization Current Transientsmentioning
confidence: 80%
See 3 more Smart Citations
“…1. A series of calibration measurements on small samples of known area showed that -c --KSA [1] where 8A is the area of metal being anodized, and K, for our experimental arrangement, had a value of 300 mse c/cm 2.…”
Section: Reanodization Current Transientsmentioning
confidence: 80%
“…From these relationships it is easily shown that for our specimen geometry 8A = 0.57 ex [4] A Combining Eq. [1] and [4], the value of T/A --170 el msec/cm 2. Thus for a tensile strain of 6 X 10 -3 , 9 /A = 10.2 msec/cm 2.…”
Section: Reanodization Current Transientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fundamental research on the features of the anodic barrier films formed in the bases of boric acid, [13][14][15][16][17] citric acid, 18,19 tartaric acid, 1,[20][21][22] phosphoric acid, 23,24 and ammonium adipate electrolytes, 25,26 and so forth, are comprehensive. Katoh 27 summarized the performance of the aluminum oxide films formed in various electrolytes.…”
Section: Introductionmentioning
confidence: 99%